(untitled) (Journal of Comparative Social Work, 2016)
The article reports on a qualitative study of Roma employability in Romania. Being the largest ethnic minority group in Europe, the Roma population is the object of profound marginalization in most of the countries where they reside, by measures such as spatial segregation and exclusion from the formal labour market. This article focuses particularly on the Roma living in rural segregated communities. Inspired by institutional ethnography, the aim is to explore the social organization of rural Roma employability from the standpoint of the Roma themselves. The main obstacles to employment, as they are known and shared by our interviewees, are a lack of available jobs within reach, their own lack of education and a rejection by employers on the grounds of them being Roma. As the analyses show, these obstacles, and the individual’s experiences and knowledge about them, are shaped and maintained by extended translocal relations of administration and governance, thus making the rural Roma dependent on a precarious secondary labour market of low-paid day work for neighbouring farmers. The uncertainty of this work, and the organization and work of everyday life it implies for the people inhabiting these communities, further increases the distance to formal employment. It is this complex set of relations coordinating people’s doings that produce the employability of Roma inhabiting the rural segregated communities.